HISTORIANS' INTEREST IN INTERPRETATION AND QURANIC SCIENCES (IBN ASAKIR AS A MODEL) - Dr Sadia Gul (Journal of Religion and Society, 2025)
The article titled "The Historians' Interest in Quranic Interpretation and Sciences (Ibn Asakir as a Model)" examines the focus of historians, particularly Imam Ibn Asakir, on the sciences of Quranic interpretation (Tafsir) and Quranic studies. It highlights his contributions through his encyclopedic work, "Tarih Madinat Dimashq" (The History of Damascus). The study is organized into several sections: Introduction to Ibn Asakir and His Historical Work: It provides an overview of Ibn Asakir's scholarly background, upbringing in a learned environment, and his monumental book, The History of Damascus, as an encyclopedic reference encompassing Hadith, linguistics, history, and Quranic interpretation. Ibn Asakir's Focus on Tafsir and Quranic Sciences: The article explores his significant interest in Tafsir bil Ma'thur (interpretation based on transmitted traditions) and its divisions, emphasizing his methodology in interpreting the Quran through the Quran itself, the Prophetic traditions, and the sayings of the Companions and Followers. Strengths and Critiques: The research highlights the merits of Ibn Asakir’s work, such as documenting approximately 3,000 interpretive narrations and critically analyzing them, while also pointing out some methodological shortcomings. The article underscores Ibn Asakir's pivotal role in blending historical scholarship with Quranic sciences, demonstrating his significant contribution to preserving the interpretive heritage through a comprehensive and scholarly approach. Keywords: Quranic Interpretation, Emphasizing, Historical, Interpretive Narrations, Demonstrating, Significant, Contribution